Robitnytsia, Ukrainian Communists, and the 'Porcupinism' Debate: Reassessing Ethnicity, Gender, and Class in Early Canadian Communism, 1922-1930 - Sangster, Joan (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2005)
Abstract This article explores the connections between ethnicity, gender, and class in the Communist Left from the founding of the Canadian Communist Party to the advent of the Third Period in the early 1930s. Within the Communist Party, ethnicity was a contested and complex relationship; while the Ukrainian section of the Party was numerically very strong, it was also disparaged as too 'separatist and culturalist' by the Anglo-Celtic leadership of the Party. By examining the paper produced by Ukrainians for women comrades, Robitnytsia (The Working Woman), we can examine the way in which gender, ethnicity, and class were imagined and experienced in early Party history. The founding, evolution, and content of Robitnytsia are explored, along with its influential editor, Myroslav Irchan. Special attention is paid to an extended debate in Robitnytsia about women's equality and role in the movement, at the time termed the 'porcupinism' debate.